MENGENAL ADAT KEMATIAN/ADAT PATI NYAWA DAYAK TAMAN DI KOTA PUTUSSIBAU KABUPATEN KAPUAS HULU - Genopepa Sedia (Universitas Kapuas Sintang, 2020)
This research experience is encouraged through the prominence of the conception of Taman costum law, which is implemented firstly in Malapi Pabiring in 1959. It is succeeded to transcribe the Manpower Law in form of written book. Afterwards, a second conception is approved through an assembly in Malapi Village on 25 to 27 October 1996 to assort a customary law in form of written book. In order to adapt the development of civilization in society and toward the customary Daya’ Taman law; these are really becomes a living guide, protector, guide and becomes the necessities of the Daya’ Taman societies. Therefore, in 2008 a deliberation is conducted at Deo Soli Monastery to decide the customs and Daya’ Taman custom laws of Kapuas Hulu regency. A Custom is an idea of culture which consists of cultural values, norms, habits, institutions, and customary law which is regularly used in a group. The author is interested to execute this research entitled “Investigating the Customs of Death / Adat of “Pati Nyawa” of Dayak Taman in Putussibau City, Kapuas Hulu Regency”.What are benefits or purpose that acquired in the funeral rituals (Manaro)? What are the benefits or purpose that acquired in the death rituals (Manaro) ?, What is the impact that acquired in the Ritual of caring for the dead (Babuling) ?, How is the customs’ procession toward the Decedent (Mararak). This research is applied a normative juridical approach or literature study through learning books, laws and regulations and other documents that related to this research. Furthermore, this research is applied also a sociological juridical (empirical) approach or field of research with a descriptive analysis method. Manaro ‘/ Manjagaang (guarding the Decedent). For Daya’ Taman community, if someone died which is indirectly be laid to rest at the time, the dead body is buried after a condolence visit of grieving family (ikampir). In order to wait during an “ikampir” the dead body is laid down in front place or Ta’Soo, the dead body is guarded collectively at night by the local community and even more from other nearest villager. It usually the dead body is buried at the exactly time between three days until four days and nights to carry out the customs procession based on biography of the decedent. After a condolence visit of grieving family (ikampir), The dead body is delivered Genopepa Sedia, Mengenal Adat Kematian/Adat Pati Nyawa 63 to the grave. Moreover, there are still people who gather together called “mandudukang / manaro’d” carry out traditional processions on the first night after the dead body is delivered. The custom of “pati Nyawa” refers to someone who consciously “muno’ ” kills people / kills deliberately are imposed to customary sanctions including: 1. Pay Pati Nyawa Rp. 45,000,000; 2. Pay the burial fee of Rp. 20,000,000; 3. Paying the cost of release taboos / mararak Tata Rp. 15,000,000; 4. Then the total is Rp. 80,000,000.00. Keywords: Custom, Pati Nyawa, Dayak Taman.